On the discriminatory and predictive accuracy of the RDT against the microscopy in the diagnosis of malaria among under-five children in Nigeria (2019)
Background: Accurate identifcation of malaria cases is crucial to the management of cases and the eventual success of malaria eradication agenda. This study is designed to evaluate the discriminatory and predictive accuracy of malaria rapid diagnostic tests (RDTs) in Nigeria. Methods: The data obtained during the 2015 Nigeria Malaria Indicator Survey was used to quantify the discriminatory accuracy of the RDT against the microscopy through the analysis of its sensitivity, specifcity, positive (LR+) and negative (LR−) likelihood ratio. The positive (PPV) and negative (NPV) predictive values, area under the receiver operating characteristic curve, and diagnostic odds ratio were used to assess the predictive accuracy of the RDTs using expert microscopy as a gold standard at p=0.05. The McNemar paired test and the Kappa statistics were used to assess the level of agreement between the diagnostic tests. Results: There was a significant but not an excellent agreement between the results of the RDT and microscopy tests (p<0.001). The overall sensitivity of the RDT was 87.6% (85.9–89.2%), specificity was 75.8% (74.4–77.1%), while the diagnostic accuracy stood at 79.0% (77.9–80.0%). The LR+, LR−, PPV and NPV were 3.6 (3.4–3.8) and 0.16 (0.14–0.19), 57.5% (56.1–58.9%) and 94.2% (93.5–94.9%), respectively. The sensitivity of RDT increased as the age of the children increased, from 85.7% among those aged 0–6 months to 86.1% in 7–23 month olds to 88.1% among those aged 24–59 months, but the reverse was the specificity. For children with severe anaemia, the sensitivity of the RDT was nearly 100% compared with a specificity of 39%. While the sensitivity and the PPV reduced with children’s level of anaemia, the higher the severity of anaemia, the lower the NPV, specificity, the diagnostic accuracy of the RDT. The odds of RDT being sensitive was about 50% [adjusted Odds Ratio (aOR)=0.52 (95% CI 0.30–0.90)] lower among children aged 7–23 months compared with those aged 24–59 months while the odds of RDT being sensitive was 2 times [aOR=2.15 (95% CI 1.67–2.77)] higher among those 7–23 months than among those aged 24–59 months. Conclusions: Although there was a significant agreement in the outcomes of RDT and microscopy tests, the discriminatory accuracy of RDT was weak. Also, the predictive accuracy, especially the PPV of the RDTS, were very low. These measures of accuracies differed across the age of the children, level of anaemia, recent experience of malaria and other characteristics. Without an accurate, efficient and reliable diagnosis of malaria, the goal of eliminating malaria and reduction of malaria-related deaths to zero by 2020 will only remain elusive.